1991
DOI: 10.1093/ajcn/53.6.1647s
|View full text |Cite
|
Sign up to set email alerts
|

Obesity and cardiovascular risk intervention through the ad libitum feeding of traditional Hawaiian diet

Abstract: The Waianae Diet Program is a community-based intervention strategy designed to be culturally appropriate by using a pre-Western-contact Hawaiian diet to reduce chronic-disease risk factors in Native Hawaiians. This paper describes a trial of the traditional Hawaiian diet fed ad libitum to Native Hawaiians with multiple risk factors for cardiovascular disease to assess its effect on obesity and cardiovascular risk factors. Twenty Native Hawaiians were placed on a pre-Western-contact Hawaiian diet for 21 d. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
68
0
1

Year Published

1994
1994
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 110 publications
(74 citation statements)
references
References 28 publications
4
68
0
1
Order By: Relevance
“…Similar reductions in obesity and cardiovascular risk have been observed when natives in Hawaii have returned to a traditional diet after abandoning the usual modern diet (132).…”
Section: Ethnicitymentioning
confidence: 57%
“…Similar reductions in obesity and cardiovascular risk have been observed when natives in Hawaii have returned to a traditional diet after abandoning the usual modern diet (132).…”
Section: Ethnicitymentioning
confidence: 57%
“…They include: a reduction in compliance to the diet, perhaps due to an environment that is unsupportive of healthy food choices; overeating of foods known to be low in fat and; physiological adaptations that attenuate the impact of negative energy balance on weight loss 78 . Extremely low fat, high carbohydrate diets are also very effective for weight loss 79,80 but it must be stressed that large reductions in total fat intake would be unattainable at a population level. Average changes in the order of 2-3 kg may seem small for individuals but they are important on a population level in the context of obesity prevention.…”
Section: Early Nutritionmentioning
confidence: 99%
“…A number of feeding studies that have manipulated dietary energy density have suggested that a decrease in energy density is associated with weight loss (14,15). Although these feeding studies have addressed important questions about the association between energy density and weight loss, longer term studies of individuals eating in real-life situations are necessary to test the hypothesis.…”
Section: Introductionmentioning
confidence: 99%